Scalable combustion synthesis of graphene-welded activated carbon for high-performance supercapacitors - Li, Chen (2022)
State-of-the-art supercapacitors mainly employ various activated carbons as active electrode materials; however, few of them can simultaneously exhibit superior electrical conductivity and tailored porosity to offer both high energy and power performance. In this work, we demonstrated a scalable combustion synthesis to manufacture graphene-welded activated carbon in CO2 atmosphere using Mg as sacrificial solder. The electrical conductivity of graphene-welded activated carbon reaches 2836 S m−1, and a hierarchical porous structure is achieved via simply changing the starting conditions of combustion synthesis. These appealing attributes guarantee substantially enhanced ion diffusion and electron transport throughout the carbon matrix, thus delivering a superior energy density of 80 Wh kg−1 and high power density of 70 kW kg−1. The scalable combustion synthesis opens a new avenue to produce high-performance activated carbon materials for future energy-storage devices.